(untitled) (The University of Nairobi Journal of Language and Linguistics, 2023)
From a variety of sources, this paper has gleaned a substantial amount of information on specific aspects of the vocabulary of the Kenyan English variety. This information provides evidence that as a second language variety Kenyan English has developed its vocabulary through the main processes of a) borrowing from indigenous languages, b) coining its own words and phrases, and c) giving, to a number of international English words, additional meanings that are specific to it. The loan words from indigenous languages are no doubt more visible than the other two components of Kenyan English vocabulary, but they are numerically much less important than these two.